A COMPARATIVE STUDY OF EMOTIONAL INTELLIGENCE AND PARENTAL ATTITUDE OF PRE-SECONDARY SCHOOL GIRLS OF URBAN AND RURAL AREAS ON THEIR EDUCATIONAL ACHIEVEMENTS - Verma, Sarita; Bhatnagar, Shivani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Education is the key to social harmony and development in a society, and girls play an important role in it. Our study attempts to understand the relationship between emotional intelligence and parental attitudes of girls educated in pre-secondary schools in urban and rural areas. The study aims to understand how emotional intelligence of girls and their parents’ attitudes differ in urban and rural areas, and what impact this difference has on education. We have conducted a comparative study of emotional intelligence of girls in pre-secondary schools in urban and rural areas. The study showed that girls in urban areas have more developed emotional intelligence than those in rural areas in self-evaluation, social integration, and social awareness. At the same time, we also focused on the attitudes of the parents of girls. The research has shown that parents in urban areas are actively involved in the education of girls and encourage their achievements, while this is lacking in rural areas. The research has shown that this difference in emotional intelligence and parental attitudes leads to differences in education. Girls in urban areas are more engaged and successful in education when their parents are actively involved and encourage them in education. From this study, we conclude that there is a difference between the emotional intelligence of girls in urban and rural areas and the attitudes of their parents, and this difference has a direct impact on education. This can provide suggestions towards social and economic equality in education so that every girl child gets the opportunity to overcome her limitations.